Evaluation of Marginal Microleakage for Bulk-Filled Composite Restorations on Primary Molars (in vitro study) (Journal of Hama University, 2020)
The aim of this study was the comparison of the marginal microleakage of class II bulk-filled composite restorations on primary molars. 32 standardized class II cavities were prepared on primary molars and divided into two groups 16 for each. Group (1) was restored by conventional composite (Arabesk-Voco) applied in one bulk technique, and group(2) was restored by Bulk-fill composite (Xtra-fil – Voco) applied also in one bulk technique. Phosphoric acid 37% (META) and the bonding agent (Solo bond M-Voco) was used in all specimens. After 500 water cycle and immersing in 0.5% methylene blue, all teeth was sectioned mesio-distally in order to evaluate dye penetration on the gingival and occlusal margins. Dye penetration was evaluated by a scale (0,1,2,3) and data was collected and analyzed by SPSS version 24. None of the two materials was able to prevent the dye penetration on the gingival or occlusal margins. According to Mann-whitney test, no significant difference was observed in term of dye penetration between the two groups either on gingival margins (P=0.632) or occlusal margins (P=498). The comparison between the gingival and occlusal margins in each group using Wilcoxon test shows higher leakage on the gingival margins in the two groups, group (1) (P=0.042), group (2) (P=0.005). We concluded that the Bulk-fill material (Xtra-fil) did not show significantly higher results in terms of marginal microleakage in small class II cavities on primary molars.